Implementation Of Children's Special Needs For Religiusity In Specific Training And Development Parks Abk Probolinggo: Implementasi Nilai-Nilai Religusitas AnakBerkebutuhan Khusus Di Taman PelatihanDan Pengembangan Abk - Muhammad, Devy Habibi; Dheasari , Agustiarini Eka (Halaqa: Islamic Education Journal, 2020)
The purpose of this study was to determine, First, the Implementation of the inculcation of religious values ​​of children with special needs consisting of worship values, moral values ​​and scientific values. Second, the implementation of the inculcation of religious values ​​in supporting social activities of children with special needs with family and community. Third, the problem of inculcating religious values ​​of children with special needs. A teacher must be able and patient in instilling the values ​​of religiosity, especially the faith. The application of the inculcation of religious values, namely faith, morals and worship in children with special needs, teachers uses several different methods that are adapted to the situation and condition of the child, mentl, mood, and physical so that the inculcation of religious values ​​can be accepted and attached to the child. . The activities of children with special needs in supporting children 's socialization activities have been carried out and are well established, children are invited by the teacher to interact both with their peers or with the community by inviting them to walk around in the complex near the school. difficulties experienced in the process of inculcating religious values ​​of children with special needs such as worship, faith, and moral values ​​are caused by communication factors. Keywords: Implementation of Values ​​of Religiosity, Children with Special Needs